Jonah and Tobit A developing understanding of the meaning of exile - Henderson, Ruth Margaret (2022)
Although much has been written on the biblical influences on the Book of Tobit, little scholarly attention has been paid to the similarities between the books of Jonah and Tobit, apart from the common term “great fish.” The following study draws attention to the similarities between these two books in terms of their date, narrative strategy, genre, background, worldview, and ideology, and in particular, their use of the unique term “great fish.” The motif of the fish is of great significance in both books, as it sheds light on the exilic background of both works.
Keywords: Septuagint; Nineveh; Jerusalem; Hellenistic Period; Exile; aretalogy